An investigation on production routes of U-230 radioisotope used in targeted alpha therapy by different level density models - Özdoğan, Hasan; Şekerci, Mert; Cinoğlu Karaca, Merve; Okutan, Murat; Demir, Bayram; Kaplan, Abdullah (Pleiades Publishing Inc, 2022)
Targeted alpha therapy (TAT) is an attractive therapeutic option in patients with multiple micrometastases. It offers many advantages, including easy administration, the ability to treat multiple lesions simultaneously and the possibility of combination with other therapeutic approaches for improved efficacy. The aim of this study is to investigate the optimum production route of U-230, which is a promising TAT isotope, in cyclotrons. For this, Pa-231(p, 2n)U-230, Pa-231(d, 3n)U-230, Th-232(p, 3n)Pa-230, and Th-232(d, 4n)Pa-230, reactions cross-sections, total activity and reaction yield have been calculated by using different level density models of TALYS 1.95 code. It is possible to produce an U-230 activity of 53.491 mCi via on Pa-231(p, 2n)U-230 direct route with 12.8 MeV protons at 1 mA current for 24 h. After a 28 days waiting period required for undesirable product (U-230) activity to decrease sufficiently, this activity decreases to 21.4 mCi and by considering the average dose per patient as 0.5 mCi, these activities are enough for 43 patients. Besides, Pa-231 is already the target material in this direct production route and Pa-231 obtained from undesirable product U-231 can be stored and processed for re-use as the target material. In this way, a significant amount of source material can be recovered.
Keywords: U-230; Alpha Therapy; Density Models; Production Routes